BUSINESS MANAGERS COMPETENCES: ITS DEVELOPMENT PROCESS AND LABOR MARKET DEMANDS - Martins-Silva, Priscilla de Oliveira; Silva, Camila Santos; Silva Junior, Annor da (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
It was investigated the point of view of business managers registered at the Regional Administration Board at Espírito Santo state (RAB/ES) about individual competences for work and professional practice. It was used the fifteen competences identified by Sant´Anna; Moraes and Kilimnik (2005) as a reference. It was investigated two complementary perspectives on competences: the development process of competences and labor market required competences. The research was characterized as an intersectional survey and data were collected through questionnaire. The results indicate that the fifteen individual competences are demanded in great scale by labor market according to all respondents surveyed. Regarding the development process of competences, it turns out that much of the educational level (formal education) and life experience (non-formal and informal education) contribute to competences’ development, but life experience contributes more significantly.